THE IMPROVEMENT OF ORGANIZATIONAL SECURITY OF PROCESS OF ATTRACTING A VENTURE BUSINESS`S FORM FOR ENTERPRISE`S DEVELOPMENT IN THE CONDITIONS OF ECONOMY`S DIGITALIZATION - CHEREDNYK, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The necessity for improving the existing organizational framework for engaging venture business forms is justified, aiming to facilitate the implementation of new technologies, elevate production to a higher level, and enhance the competitiveness of enterprises in both domestic and international markets. The organizational support for involving venture business forms in the development of industrial enterprises in the conditions of economic digitization is enhanced. A scheme for selecting the organizational form of venture business and funding sources is proposed, allowing the utilization of digital transformation tools to increase the effectiveness of venture business engagement. Venture business is defined as entrepreneurial activity involving the infusion of risky investments into the innovative development of a knowledge-intensive industry, prone to potential growth. The following organizational forms of venture business are identified: "independent ventures," "external ventures," and "internal ventures". Various types of organizational forms of venture business and sources of their funding are considered. The engagement of venture business forms is carried out through financing the venture using various capital sources, specifically from the company’s cash fund, funds from venture investors, and funds obtained from a venture fund. Using the PATTERN method, a goal tree for each form of venture business and funding source is constructed. The cost forecast for organizing an internal venture with funding from the company’s own financial resources is conducted. The author also proposed an alternative venture financing option using the company’s funds, such as raising funds from a venture fund through the sale of 10–20% of the company’s shares. The proposed measures will enable industrial enterprises to overcome their crisis and become competitive in both external and internal markets.